Brand Trust over Price Consciousness: Driving Generation Z Brand Loyalty in Online Travel Agencies - Lady Lady; Vanessa Stephanie; Wisnu Yuwono (International Journal of Marketing & Human Resource Research, 2026)
While digital platforms frequently employ aggressive pricing to capture the Generation Z market, prior research yields inconsistent evidence on whether economic incentives or psychological factors more effectively secure long-term commitment. This study addresses this gap by examining the interplay between brand communication, online reviews, and brand loyalty, with brand trust as a mediator and price consciousness as a moderator. Using a quantitative approach, data were collected from 193 Gen Z consumers and analyzed through partial least squares structural equation modeling (PLS-SEM). The novelty of this research lies in identifying a "full mediation" mechanism: the findings reveal that brand communication and online reviews have no direct effect on brand loyalty, as their influence is entirely mediated by brand trust. Furthermore, this study uncovers a significant resilience against price-driven strategies, as price consciousness demonstrated no significant direct or moderating effect on the trust-loyalty relationship. This contradicts the prevailing assumption that Generation Z's purely price-sensitive and highlights that, for digital natives, platform integrity and reliability serve as the ultimate anchors of loyalty. These insights suggest that online travel agencies must pivot from price-centric models toward trust-centric architectures to maintain competitive advantages.